Gene Cloning and DNA Analysis : An Introduction (Wiley-Blackwell, 2010)
Known world-wide as the standard introductory text to this important and exciting area, the sixth edition of Gene Cloning and DNA Analysis addresses new and growing areas of research whilst retaining the philosophy of the previous editions. Assuming the reader has little prior knowledge of the subject, its importance, the principles of the techniques used and their applications are all carefully laid out, with over 250 clearly presented four-colour illustrations. In addition to a number of informative changes to the text throughout the book, the final four chapters have been significantly updated and extended to reflect the striking advances made in recent years in the applications of gene cloning and DNA analysis in biotechnology. Gene Cloning and DNA Analysis remains an essential introductory text to a wide range of biological sciences students; including genetics and genomics, molecular biology, biochemistry, immunology and applied biology. It is also a perfect introductory text for any professional needing to learn the basics of the subject. All libraries in universities where medical, life and biological sciences are studied and taught should have copies available on their shelves. \\\\\\\\\\\\\\\ÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬Ãƒâ€šÃ,Â¦ the book content is elegantly illustrated and well organized in clear-cut chapters and subsectionsÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬Ãƒâ€šÃ,Â¦ there is a Further Reading section after each chapter that contains several key referencesÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬Ãƒâ€šÃ,Â¦ What is extremely useful, almost every reference is furnished with the short but distinct author\\\\\\\\\\\\\\\'s remark.\\\\\\\\\\\\\\\ ÃƒÆ'Ã,Â¢ÃƒÂ¢Ã¢â,¬Å¡Ã,Â¬ÃƒÂ¢Ã¢â€šÂ¬Ã...â€œJournal of Heredity, 2007 (on the previous edition)